Political Economy of Agrarian Crisis and Slow Industrialization in India - Sudipta Bhattacharyya; Mathew Abraham; Anthony D'Costa (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2013)
This paper uses the structuralist framework of agriculture-industry synergy in an economy to discuss the performance of the agricultural and industrial sectors in India. The industry - agriculture relationship is argued to be integral to economic development as the agriculture sector supplies raw materials, surplus labour to the industrial sector and acts as a source of demand for industrial goods. However, in India this relationship has been complex. This paper looks at the supply side constraints in the agricultural sector and the demand side constraints in the industrial sector to assess the poor development and growth in the two sectors. It concludes that India has not followed the structuralist pattern of sectoral development and poor agricultural growth has not been conducive for demand led industrialization, adversely affecting factor markets for both labour and land.
hdl:10398/8642
Keywords: 330; India; Industry-agriculture linkages; Liberalisation; Demand constraints; Growth; Landwirtschaftliche Entwicklung; Industrialisierung; Wirtschaftsstruktur; Agrarpolitik; Industriepolitik; Indien